If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -2 = 8 + y Reorder the terms: -2 + 3y = 8 + y Solving -2 + 3y = 8 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -2 + 3y + -1y = 8 + y + -1y Combine like terms: 3y + -1y = 2y -2 + 2y = 8 + y + -1y Combine like terms: y + -1y = 0 -2 + 2y = 8 + 0 -2 + 2y = 8 Add '2' to each side of the equation. -2 + 2 + 2y = 8 + 2 Combine like terms: -2 + 2 = 0 0 + 2y = 8 + 2 2y = 8 + 2 Combine like terms: 8 + 2 = 10 2y = 10 Divide each side by '2'. y = 5 Simplifying y = 5
| -7(v+5)=-5v-25 | | 4(x-3)=7x+6 | | 10/12/1/4= | | 3(x-3)=5x+8 | | 3/4-1/3+(-5/24)= | | 11(3x^2-x-2)=0 | | 40=x(3x-7) | | 2.4+1.2x=15 | | 12x^2-5=17 | | 3n+n=27 | | 60x-3x^2=10x+2x^2 | | 80x-3x^2=10x+2x^2 | | (6+4n-4)n=1806 | | a/4+3=a/3+5 | | 27.9/6.2 | | 200/18x22000 | | z/4+3=z/3+7 | | 2x=18-4x | | 2(y+3)+3y=5y-10 | | 25g-100=-75 | | 5n+10=-65 | | 2x+2=x-3 | | 7(9x-5)-3(4-8x)+7(-4x+6)=-10(2-6x) | | (3/y^2-9)+(4/y+3)=1 | | 4n+6=-22 | | 37-x=2a | | 1/2(4y+6)-5=-1/7(7y-28) | | 1n-2=2n | | 6-2x=2x+4 | | 24x+5=1 | | x^2-4x-4=0whatisx | | 16/2/3 |